Needs Analysis of English for Specific Purposes Course in Home Economics Based on Graduate Users' Perceptions - Sita Nurmasitah; Pudji Astuti; Ririn Setyowati (Jurnal Penelitian Pendidikan, 2024)
The study aims to identify and analyze the specific English language learning needs of students in higher education in Home Economics based on the perceptions of graduate users. Utilizing a quantitative approach, the research employs a questionnaire as the primary data collection tool. This questionnaire was administered to graduate users of the Home Economics Program at the Faculty of Engineering, Universitas Negeri Semarang, with respondents including twelve individuals from diverse sectors such as schools, government offices, private companies, and home industries or SMEs. The findings reveal that the need for English proficiency varies by sector. In educational settings, English is vital for understanding instructional materials and meeting global educational standards. For government offices, proficiency in English is essential for international collaboration, effective communication in meetings, and maintaining global partnerships. Private companies, particularly multinational corporations, rely on English for recruitment, daily operations, and interactions with international clients, even though incentives for language proficiency are often lacking. Meanwhile, in-home industries, although English is not yet a strict requirement, it is becoming increasingly important for online marketing, responding to international inquiries, and engaging with promotional media. As globalization and technological advancements continue to reshape these sectors, the study underscores the growing necessity of English proficiency. The findings highlight the critical role that English plays in enhancing professional effectiveness and competitiveness, making this research an essential contribution to curriculum development and workforce readiness in an increasingly interconnected world.